Identity: Culture Paradigm and Professional Space - Zheleznyak, Olga (project baikal, 2014)
The article considers identity as a system of selfdetermination in the global/local opposition. The ‘identification resource’ inherent in the historical environment is presented as a specific feature of modern territorial entities, architecture, as well as objectivespatial environment to identify them with a certain space or place. The means of cultural formation and translation of the identity resource are set up through the concept of the ‘transmutation contact’, which captures the essence of the processes of new creation and formation. Nomadism as another pole of the global/local opposition and a new interpretation of the space of sedentism assigns new ideals of development and forms of identification. Discourses of self-determination as a part of the global/local space are proposed to be interpreted as a key tendency in the development strategies of the region and the design culture.
Keywords: global dichotomy; local dichotomy; identity; resource ideology; transmutation; nomadology; visualization of identity images